A new classification system for biomass and waste materials for their use in combustion - Jenkinson, Philip (2016)
The use of biomass derived solid fuels for electricity generation in combustion, gasification and pyrolysis plant has received increasing levels of interest for commercial operation in recent years. However, there are limited tools available which allow a prediction of the performance of these fuels during thermochemical transformation given an understanding of their original chemical structure. As such, this investigation has concentrated on the derivation of a simply utilised classification system able to predict a series of important fuel combustion characteristics given an understanding of both the organic and inorganic chemical and structural composition of any lignocellulosic biomass fuel. A prediction of volatile matter content and char yields during pyrolysis has been made using correlation with aromatic carbon, potassium and calcium contents using both thermogravimetric slow heating and simulated pulverised fuel (PF) entrained flow rapid heating. Alongside this, investigation of the impact of biomass composition, namely aromaticity and alkali/alkaline earth metal concentrations, on char structure and oxidative char reactivity of simulated PF chars has been conducted. Experimental investigation has involved the pre-treatment of a wide range of commercially available biomass fuels including softwood, hardwood, herbaceous and agricultural waste materials to remove both lignin and ion exchangeable mineral species. In addition to this, torrefaction has been utilised to increase the aromatic character of chosen fuels. This has allowed a quantification of the impact of aromaticity and mineral matter concentration on pyrolysis and char combustion reactions to be derived for a wide range of fuel aromaticity and mineral matter contents. Considerable success has been achieved in the classification of an array of lignocellulosic biomass. Accurate prediction of pyrolysis char and volatile matter yields under both slow and rapid entrained flow drop tube heating conditions have been attained using simple empirical correlations with fuel aromatic carbon and alkali/alkaline earth mineral species concentrations (K+Ca being utilised here). This classification system has relied upon the clear linear correlation observed between aromatic carbon content and char yield in the absence of mineral matter influences (R2 of 0.98 and 0.95 being observed for demineralised biomass under slow and rapid heating pyrolysis respectively). In addition to this, the relative enhancement of char yield due to mineral matter interaction with varying concentration of K and Ca within the fuel has been quantified and is used to calculate total char yields. The empirical relationship derived under slow heating takes the following form: Slow Heating Char Yield=(1×Aromatic Carbon )+(16.1 ×(K+Ca) ) Where slow heating char yield is the char yield wt% on a dry ash free basis (daf), aromatic carbon is the wt% daf aromatic carbon content of the biomass and K+Ca is the wt% K+Ca content of the raw fuel on a dry basis. This relationship applies below K+Ca contents of 0.6 wt% db, beyond this a fixed additional char yield of 9.76 wt% daf can be applied as a quantification of the influence of enhanced char yield due to mineral activity as the second term in the above equation. For rapid heating entrained flow pyrolysis the empirical prediction of char yield is conducted as follows: Rapid Heating Char Yield=(0.58×Aromatic Carbon )+(2.43 ×(K+Ca) ) Strong linear correlations of predicted vs. observed char yield have been derived with correlation coefficient R2 = 0.96 and 0.99 with mean relative errors of 7.8 and 8.4% for slow and rapid heating pyrolysis respectively. Furthermore, the influence of biomass aromaticity and active mineral content on char formation processes, the form of chars generated under PF like devolatilisation conditions and their subsequent oxidation reactivity has been studied in detail. Both alkali/alkaline earth mineral matter content (primarily K and Ca) and aromaticity are instrumental in determining the porosity, morphology and surface area of simulated PF chars. Due to its tendency to soften during heat treatment lignin is shown to produce low surface area, non-porous chars under slow heating and this behaviour drives a reduction in char surface area and combustion reactivity with increasing aromatic carbon content. Although char surface areas have been seen to be negatively correlated with increasing potassium and calcium content this may be due to ash blockage of char pore structures. However, the likelihood of a negative impact of mineral enhanced charring has been discussed. K catalysis of combustion reactions is clearly evident in apparent and inherent char reactivities; however, easy quantitative assessment of this influence has been prevented by the clear complexity of mineral behaviour during the pyrolysis process. The development of char structure and reactivity as a function of char combustion degree has also been investigated under entrained flow combustion conditions. The results of this study indicate that by accurately quantifying aromatic carbon, potassium and calcium contents, all lignocellulosic fuels can be classified in terms of their behaviour during pyrolysis (volatile matter and char yields), the form of char structures generated (surface area and porosity) and char combustion reactivity. It is hoped that this relative classification will shed light on the predicted performance of biomass fuels for use in combustion driven power generation infrastructure, especially in pulverised fuel applications.